Beneficial and Harmful Interactions of Antibiotics with Microbial Pathogens and the Host Innate Immune System - Ronald Anderson; Gregory Tintinger; Riana Cockeran; Moliehi Potjo; Charles Feldman (MDPI AG, 2010)
In general antibiotics interact cooperatively with host defences, weakening and decreasing the virulence of microbial pathogens, thereby increasing vulnerability to phagocytosis and eradication by the intrinsic antimicrobial systems of the host. Antibiotics, however, also interact with host defences by several other mechanisms, some harmful, others beneficial. Harmful activities include exacerbation of potentially damaging inflammatory responses, a property of cell-wall targeted agents, which promotes the release of pro-inflammatory microbial cytotoxins and cell-wall components. On the other hand, inhibitors of bacterial protein synthesis, especially macrolides, possess beneficial anti-inflammatory/cytoprotective activities, which result from interference with the production of microbial virulence factors/cytotoxins. In addition to these pathogen-directed, anti-inflammatory activities, some classes of antimicrobial agent possess secondary anti-inflammatory properties, unrelated to their conventional antimicrobial activities, which target cells of the innate immune system, particularly neutrophils. This is a relatively uncommon, potentially beneficial property of antibiotics, which has been described for macrolides, imidazole anti-mycotics, fluoroquinolones, and tetracyclines. Although of largely unproven significance in the clinical setting, increasing awareness of the pro-inflammatory and anti-inflammatory properties of antibiotics may contribute to a more discerning and effective use of these agents.